P22 Childhood socioeconomic position and adult smoking: are childhood cognitive ability, psychosocial adjustment and parental involvement important?. (16th November 2010) - Lacey, R; Cable, N; Stafford, M; Bartley, M; Pikhart, H
Abstract : Background: Studies have shown that childhood socioeconomic position (SEP) is related to smoking in adulthood, independent of adult SEP. Educational attainment partially mediates this association; however, previous studies suggest three childhood factors which may also be important-childhood cognitive ability, psychosocial adjustment and parental involvement. Objective: To assess whether childhood psychosocial adjustment, cognitive ability and parental involvement are important in the association between childhood SEP and adult smoking status, over and above educational attainment. Data, Participants and Variables: Data on 7709 participants from four sweeps of the 1958 National Child Development Study were used for this study—birth (1958), age 7 (1965), age 16 (1974) and age 42 (2000). Childhood SEP was indicated using father's social class at birth and adult smoking status was taken at age 42 years (categorised as: 1 never/infrequent smokers, 2 ex-smokers, 3 current smokers). All childhood factors investigated were measured at age 7 years. Childhood cognitive ability was measured using score in the Copying Designs Test, psychosocial adjustment was measured using the teacher-assessed Bristol Social Adjustment Guide (BSAG) and parental involvement was based on questions asked of the mother and father regarding the frequency of occasions spent reading and on outings with the child. Confounding variables included were mother's smoking, age at birth of child and educational level, number of siblings and participant's own educational attainment at age 16 years (indicated by exam scores). Those with complete data on all variables used were included in the analysis. Statistical Methods: Multinomial logistic regression was used to examine the associations of childhood SEP and childhood factors with adult smoking status, both independently and mutually adjusted, and then adjusted for confounders and participant's educational attainment. Analyses were conducted separately for men and women. Results: Childhood SEP was an important predictor of current adult smoking status, even after adjustment for childhood factors and educational attainment. Also, parental involvement for men (most vs least frequent parental reading OR 0.75, 95% CI 0.60 to 0.94; most vs least frequent parental outings OR 0.55, 95% CI 0.35 to 0.86), and both parental involvement (most vs least frequent parental reading OR 0.68, 95% CI 0.55 to 0.85) and psychosocial adjustment (most vs least maladjusted OR 1.28, 95% CI 1.01 to 1.64) for women, remained important determinants of current adult smoking over and above childhood SEP, other childhood factors and educational attainment. Conclusions: These findings suggest that childhood disadvantage is associated with adult smoking behaviours and the early childhood social environment is important in the development of these.